Persepsi Guru MA Raudlatul Ulum 2 Gondanglegi terhadap Bank Syariah - Putri Wulan Suci; Robiatul Adawiyah; Putri Nadiyatus Sholihah (Jurnal Akuntansi dan Bisnis Syariah, 2024)
This study aims to explore the perceptions of teachers at Madrasah Aliyah (MA) Raudhatul Ulum 2 Gondanglegi towards Islamic banks. The research method used is qualitative research, where data were collected through in-depth interviews with the Principal, School Treasurer, and Homeroom Teacher of Class XI MA Raudhatul Ulum 2 Gondanglegi. The results of the study indicate that teachers have diverse views on Islamic banks. The Principal and Homeroom Teacher of Class IX view Islamic banks positively. The Principal emphasizes the social function of Islamic banks in supporting religious activities such as the Hajj and the Homeroom Teacher of Class XI views Islamic banks as riba-free banks. In contrast, the School Treasurer considers Islamic banks as less popular institutions and has procedures that are considered complicated, which reduces interest in using Islamic banking services. These findings indicate that although Islamic banks have great potential in providing financial solutions that are in accordance with Islamic principles, challenges in terms of understanding and user experience remain major barriers to wider adoption among the community.